2013
DOI: 10.12691/ajcea-1-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Dust as Construction Material in Rigid Pavement

Abstract: Ceramic dust is produced as waste from ceramic bricks, roof and floor tiles and stoneware waste industries. Concrete (M35) was made by replacing % (up to 30%) of cement (OPC 53) grade with ceramic dust (passing 75µm) shows good workability, compressive strength, split-tensile strength, flexural strength and elastic modulus. In this experimental investigation, concrete specimens were tested at different age for different mechanical properties. The results show that with water-cement ratio (0.46), core compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
(12 reference statements)
2
13
0
Order By: Relevance
“…As shown in Figure 11, the final cracking patterns are markedly different for the lower shear strength cases (ST ratio of 1 or 2) as compared to the higher shear strength case (ST ratio of 3). The final damage pattern from the higher shear strength case agrees very well with experimental evidence [35] and the numerical result by other researchers [29]. The next factor examined is the fracture energy ratio between the Mode-II and the Mode-I for the cohesive model, herein referred to as SE ratio.…”
Section: Parametrisation Of Other Important Materials Properties 456supporting
confidence: 83%
“…As shown in Figure 11, the final cracking patterns are markedly different for the lower shear strength cases (ST ratio of 1 or 2) as compared to the higher shear strength case (ST ratio of 3). The final damage pattern from the higher shear strength case agrees very well with experimental evidence [35] and the numerical result by other researchers [29]. The next factor examined is the fracture energy ratio between the Mode-II and the Mode-I for the cohesive model, herein referred to as SE ratio.…”
Section: Parametrisation Of Other Important Materials Properties 456supporting
confidence: 83%
“…Sieve analysis of powdered form ceramic waste and lime was carried out and result shows that 98.5% of ceramic powder and 58.37% of lime passed through 75µ Sieve as per the Indian codal provision (MORT&H 2012, IS 2386). The chemical properties of the ceramic waste were considered as mentioned [1].…”
Section: Methodsmentioning
confidence: 99%
“…As reported, Indian ceramics industry, which is comprised of wall and floor tiles, sanitary ware, bricks and roof tiles, refractory materials and ceramic materials for domestic and others use is producing approximately 15 to 30 MT per annum waste. The state of Gujarat accounts for around 70% of total ceramic production in India and out of total production 30% goes as waste and dumped in the open spaces [1]. The advantages of using ceramic waste dust in road construction as mineral filler are: (i) the ceramic dust available at zero economic cost, (ii) chemical and mechanical properties will be consistent, (iii) road construction activity approaches to become green, (iv) durable, hard and highly resistant to biological, chemical and physical degradation forces [2].…”
Section: Introductionmentioning
confidence: 99%
“…In order to use PP as a replacement for cement in concrete, its effect on the properties of cement paste need to be clarified, for example, nucleation or growth-inducing factor of hydrates on their surface in early-age concrete is important because it can affect the properties of late-age concrete. Many relevant studies [4][5][6][7][8][9][10] have been conducted. Tydlitát et al [7] reported that using more than 20% ceramics in blended cement does not affect the compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Tydlitát et al [7] reported that using more than 20% ceramics in blended cement does not affect the compressive strength. In a study performed by Fatima et al [9], concrete was made by replacing up to 30% of the cement with PP resulting in concrete that had good workability, proper compressive strength, split-tensile strength, flexural strength, and elastic modulus. A study by Cheng et al [4] showed that the permeability resistance of concrete mixed with PP is superior to that of a control group, and the most desirable permeability resistance was achieved when the cement substitution rate was 30%.…”
Section: Introductionmentioning
confidence: 99%